Suicide Risk, Meaning in Life, and Need for Life Respect in Adults and Elderly Among Public Hospital Outpatients in South Korea: A Cross-Sectional Survey. Issue 1 (2nd January 2017) - Kang, Kyung-Ah; Kim, Shin-Jeong; Kim Ellis, Hyon
ABSTRACT: The purpose of this study was to identify the differences in suicide risk, meaning in life, and need for life respect among three age groups (young adults, the middle aged, and the elderly) of 540 public hospital outpatients in South Korea. This was a cross-sectional study. Among these 3 age groups, we observed significant differences in suicide risk, meaning in life, and need for life respect according to education level, marital status, living arrangements, type of disease, gender, and monthly income. These findings might contribute to the prevention of suicide in the future and the implementation of better community-based nursing care.